LITERATURE REVIEW: GAYA KEPEMIMPINAN EKSPATRIAT TIONGKOK DALAM MEMIMPIN PERUSAHAAN - Hasbullah, Farhan; Perkasa, Didin Hikmah (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to analyze the leadership styles of Chinese expatriates managing multinational companies. The primary focus is on how Chinese cultural values, such as Confucianism, collectivism, and guanxi, influence their leadership approaches and the cross-cultural adaptation challenges they encounter. Data was collected through a literature review of 8 relevant previous studies. The method used is a comparative literature review to synthesize findings. The results show that Chinese expatriates' leadership style is characterized by hierarchical and collective approaches, but flexibility and adaptation to Indonesian cultural values significantly enhance cross-cultural teamwork effectiveness. This study provides recommendations for comprehensive cross-cultural training to strengthen leadership competencies in multinational corporations.